1979
DOI: 10.1021/bi00589a014
|View full text |Cite
|
Sign up to set email alerts
|

Iron-sulfur clusters in the molybdenum-iron protein component of nitrogenase. Electron paramagnetic resonance of the carbon monoxide inhibited state

Abstract: Carbon monoxide inhibits reduction of dinitrogen (N2) by purified nitrogenase from Azotobacter vinelandii and Clostridium pasteurianum in a noncompetitive manner (Kii and Kis = 1.4 X 10(-4) and 4.5 X 10(-4) and 7 X 10(-4) atm and 14 X 10(-4) atm for the two enzymes, respectively). The onset of inhibition is within the turnover time of the enzyme, and CO does not affect the electron flux to the H2-evolving site. The kinetics of CO inhibition of N2 reduction are simple, but CO inhibition of acetylene reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
181
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(199 citation statements)
references
References 36 publications
16
181
2
Order By: Relevance
“…In the case of the ␣-Ser 69 MoFe protein, the high affinity acetylene-binding site appears to have been eliminated or severely altered without significantly altering the capacity of the altered enzyme to reduce nitrogen. Also, the remaining low affinity acetylene binding site in the ␣-Ser 69 MoFe protein does not appear to be significantly altered, maintaining a K m value similar to the value previously reported by Davis et al (15) and a V max that is only slightly less than the value derived for wild-type MoFe protein (Table II).…”
Section: Nature Of the Acetylene Resistance Phenotype Elicited By Thesupporting
confidence: 82%
See 1 more Smart Citation
“…In the case of the ␣-Ser 69 MoFe protein, the high affinity acetylene-binding site appears to have been eliminated or severely altered without significantly altering the capacity of the altered enzyme to reduce nitrogen. Also, the remaining low affinity acetylene binding site in the ␣-Ser 69 MoFe protein does not appear to be significantly altered, maintaining a K m value similar to the value previously reported by Davis et al (15) and a V max that is only slightly less than the value derived for wild-type MoFe protein (Table II).…”
Section: Nature Of the Acetylene Resistance Phenotype Elicited By Thesupporting
confidence: 82%
“…First, in the case of the normal MoFe protein, acetylene is a noncompetitive inhibitor of nitrogen reduction, whereas nitrogen is a competitive inhibitor of acetylene reduction (12)(13)(14). Second, kinetic and spectroscopic evidence obtained using the unaltered MoFe protein (15,16) as well as a MoFe protein altered by amino acid substitution (17) indicates that there are two acetylene-binding sites located within the MoFe protein. In light of these observations we became interested in determining if it is possible to obtain a MoFe protein that is altered in its ability to reduce acetylene but remains capable of normal nitrogen reduction.…”
mentioning
confidence: 99%
“…Several earlier studies have suggested two binding sites on FeMo cofactor. For example, it has been proposed that two CO molecules bind to FeMo cofactor in the high CO concentration inhibited state (29)(30)(31)(32)(33). Likewise, two acetylene binding sites have been implicated from studies combining kinetics and amino acid substitutions (31,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies revealed multiple inhibitor and substrate binding sites on FeMo-cofactor, including at least two binding sites for CO (29)(30)(31)(32)(33) and acetylene (31,34,35). Two adjacent binding sites can explain the earlier reports that two or three CO molecules can be reduced and coupled to form C2 and C3 hydrocarbon products (24,26).…”
Section: Co 2 Reduction To Chmentioning
confidence: 95%
“…The trapping of substrate-derived species on FeMo-cofactor can be monitored by the change in the EPR spectrum of the FeMo-cofactor (27,36,(44)(45)(46)(47)(48)(49). In its resting state (called M N ), FeMo-cofactor is in an S = 3/2 spin state with a characteristic EPR spectrum in the perpendicular mode with g values of 4.45, 3.56, and 2.00 ( Figure 6).…”
Section: Trapping a Diazene-derived Species Bound To Femo-cofactormentioning
confidence: 99%